1985
DOI: 10.18174/njas.v33i2.16865
|View full text |Cite
|
Sign up to set email alerts
|

Growth and morphogenesis of shoot initials of Douglas fir, Pseudotsuga menziesii (Mirb.) Franco, in vitro.

Abstract: A method of micropropagation of Douglas fir is described. Differences in morphogenesis and photosynthesis were found in shoot initials that had been isolated from buds in 10 topophysical positions on 2-yr-old trees. These differences were influenced by medium composition and light intensity, and by forcing, topping or growth regulator treatment of the mother trees. Shoots originating from buds in less exposed parts of the tree generally had a higher relative growth rate, max. net photosynthesis and photochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…For instance, the higher parts of donor plant are older than the lower parts. Evers [28] has reported that shoot initials from lower parts of Pseudotsuga menziesii developed better under in vitro conditions. Explants excised from the base produce adventitious bulbs more easily than the top parts of the bulbs [3].…”
Section: Explant Position In Donor Plantmentioning
confidence: 99%
“…For instance, the higher parts of donor plant are older than the lower parts. Evers [28] has reported that shoot initials from lower parts of Pseudotsuga menziesii developed better under in vitro conditions. Explants excised from the base produce adventitious bulbs more easily than the top parts of the bulbs [3].…”
Section: Explant Position In Donor Plantmentioning
confidence: 99%
“…Nos résultats sont à rapprocher de ceux obtenus par Boulay [13] qui, lors de l'étude de l'élongation de la tige de Pseudotsuga menziesii, a montré que le charbon actif empêchait l'arrêt de croissance ; un tel effet pourrait être dû à l'action stimulante des impuretés (monophénylamines) du charbon actif. Dans le même sens, Evers [14] a montré que l'adjonction de charbon actif dans un milieu de culture avait souvent un effet sur l'organogenèse des espèces ligneuses. Il en est de même pour Picea [15] et pour Psidium guajava [16] qui ont présenté une même réponse positive en présence du charbon actif.…”
Section: Discussionunclassified